Focus on Grammar An Course for Reference and Practice - Koch, Rachel Spack (Nxb. Tp. Hồ Chí Minh, 1997)
This text combines a clear presentation of grammar at an advanced level with communicative practice. It provides guided practice of both form and meaning, for classroom or self-study, and also offers a testing programme for diagnosis and progres